Cerebellar lesions at a young age predict poorer long-term functional recovery. Issue 1 (6th March 2020) - Beuriat, Pierre-Aurélien; Cristofori, Irene; Richard, Nathalie; Bardi, Lara; Loriette, Celia; Szathmari, Alexandru; Di Rocco, Federico; Leblond, Pierre; Frappaz, Didier; Faure-Conter, Cécile; Claude, Line; Mottolese, Carmine; et al.
Abstract: Early studies on long-term functional recovery after motor and premotor lesions showed better outcomes in younger monkeys than in older monkeys. This finding led to the widespread belief that brain injuries cause less impairment in children than adults. However, this view has limitations and a large body of evidence now indicates that cerebral damages can be more harmful when inflicted at young age, during critical periods of neural development. To date, this issue has been mainly investigated in the context of focal and diffuse cortical lesions. Much less is known about the potential influence of early cerebellar damages. Several studies exist in survivor of posterior fossa tumours. However, in these studies, critical confounders were not always considered and contradictory conclusions were provided. We studied the impact or early cerebellar damage on long-term functional recovery in three groups of 15 posterior fossa survivors, comparable with respect to their tumour characteristics (type, size and location) but operated at different ages: young (≤7 years), middle (>7 and ≤13 years) and older (>13 years). Daily (health-related quality of life scale, performance status scale), motor (International Cooperative Ataxia Rating Scale, Pegboard Purdue Test) and cognitive (full-scale intelligence quotient) functioning were assessed. A general linear model controlling for age at surgery, radiotherapy, preservation of deep cerebellar nuclei, tumour volume and delay between surgery and assessment was used to investigate significant variations in outcome measures. Early age at surgery, lesion of deep cerebellar nuclei and postoperative radiotherapy had a significant, independent negative influence on long-term recovery. Tumour volume and delay between surgery and assessment had no statistically detectable impact. The negative influence of early age at surgery was significant in all domains: daily functioning (health-related quality of life scale, performance status scale), motor functioning (International Cooperative Ataxia Rating Scale, Pegboard Purdue Test) and cognitive functioning (full-scale intelligence quotient). These results support the existence of an early critical period of development during which the cerebellar 'learning machine' is of critical importance. Although the extent to which the early deficits here observed can be reversed needs now to be established, our data plead for the implementation of prompt and intense rehabilitation interventions in children operated before 7 years of age. Abstract : In patients with cerebellar surgical lesions, a controversy exists whether early damages to the cerebellar 'learning machine' are more prejudicial than late damages. Here, we show that when potential confounders are controlled for, early age at surgery (≤7 years) is an independent risk factor for poor long-term functional recovery. Graphical Abstract: